Implementasi Metode Design Thinking Pada Perancangan UI/UX Aplikasi Pendaftaran Siswa Baru Berbasis Web - Wibowo, Nurma Budi Santoso; Purwati, Yuli; Putranto, Banu Dwi (Institut Teknologi Garut, 2025)
The New Student Admission (PPDB) process at SMP Muhammadiyah Sumbang has traditionally been conducted manually, leading to various issues such as administrative errors, complicated document submission, and limited information access for prospective students and parents. This study aims to design a web-based user interface (UI) and user experience (UX) to support a more efficient PPDB process. The method used is Design Thinking, consisting of five iterative stages: empathize, define, ideate, prototype, and testing. In the empathize stage, user needs were identified through interviews, revealing key issues such as the demand for a simple registration flow, document upload features, real-time status monitoring, and transparent fee details. These insights were used in the define stage to formulate user-centered solutions. During the ideate stage, user flows and wireframes were created to visualize the registration process and required features. The developed prototype was tested during the testing stage using the System Usability Scale (SUS) method. Testing with five respondents resulted in an average SUS score of 85, placing the application in the “good” category with an “excellent” level of acceptability. The prototype effectively addresses the challenges of manual registration, enhances time efficiency, and provides an optimal user experience. The attractive and intuitive UI/UX design also has the potential to improve the school's image in the community. With this design, the web-based PPDB system not only simplifies administrative processes but also offers a long-term, flexible, and adaptive solution to evolving user needs.